1999
DOI: 10.1071/ar98165
|View full text |Cite
|
Sign up to set email alerts
|

Associative effects between forages and grains: consequences for feed utilisation

Abstract: Intake of metabolisable energy (ME) when forages and grains are fed together to ruminants may, due to digestive and metabolic interactions, be lower or higher than expected from feeding these components separately. These interactions, or associative effects, are due primarily to changes in the intake and/or the digestibility of the fibrous components of forage. Effects on voluntary forage intake (substitution effects) are usually much larger than on the digestibility of fibrous components, although the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
1
25

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(137 citation statements)
references
References 0 publications
5
106
1
25
Order By: Relevance
“…The increasing level of intake indicated that nitrogen sources and other essential ingredients might be required to sustain optimum rumen fermentation. This has been earlier reported by several studies in sheep and cattle (Kaur et al 2008;Kozloski et al 2006;Dixon and Stockdale 1999). However, the lack of any effect of concentrate proportion on the feed intake which was recorded here (P40:C60 vs P60:C40) is similar to those described by Phipps et al (1987) and Sloan et al (1988).…”
Section: Discussionsupporting
confidence: 92%
“…The increasing level of intake indicated that nitrogen sources and other essential ingredients might be required to sustain optimum rumen fermentation. This has been earlier reported by several studies in sheep and cattle (Kaur et al 2008;Kozloski et al 2006;Dixon and Stockdale 1999). However, the lack of any effect of concentrate proportion on the feed intake which was recorded here (P40:C60 vs P60:C40) is similar to those described by Phipps et al (1987) and Sloan et al (1988).…”
Section: Discussionsupporting
confidence: 92%
“…This has been previously reported by numerous workers in both sheep and cattle (Mould et al, 1983;Kolver and Muller, 1998;Dixon and Stockdale., 1999). In the present study, the higher intake by sheep fed the C25, C35 and C45 diets may have been due to higher proportion of concentrate in the diets in comparison to C15.…”
Section: Discussionsupporting
confidence: 79%
“…However, when fed twicea-day at milking, the response to feeding high amounts of concentrates is low (Fulkerson et al, 2000;Walker et al, 2001) likely due to the adverse influence on rumen environment. In this regard, feeding high levels of concentrates, over short periods during milking, causes decrease in rumen pH leading to a decrease in fibre digestion (Dixon and Stockdale, 1999). However, the effect of a drop in rumen pH is likely to be dependent on the type of fibre being fed; thus, more rapidly digested fibre is less likely to be affected than slowly degraded fibre.…”
Section: Introductionmentioning
confidence: 99%
“…It was postulated that substitution rate often increases with increasing concentrate intake [48] but this general relationship is inconsistent for high yielding grazing cows [11] in agreement with results obtained in the present study (0.59 and 0.58 kg DM pasture kg DM concentrate −1 for T7.0 and T10.5, respectively). A higher substitution rate could be explained by negative associative effects at the ruminal level [53] coupled to reductions in ruminal pH, activity or number of cellulolytic bacteria leading to a low rate of fiber digestion and pasture intake reduction [53]. In the present study, the increase in concentrate intake affected neither the degradability nor the rate of digestion of pasture NDF [54]), who suggested that the lack of response in conversion efficiency would be explained by the substitution rate.…”
Section: Dry Matter and Energy Intakementioning
confidence: 43%